Critical reflections of early childhood care and education in Singapore to build an inclusive society. Issue 2 (February 2021) - Ang, Lynn; Lipponen, Lasse; May Yin, Sirene Lim
The early childhood years are pivotal as they mark the beginning of a young child's life journey into education. This paper offers critical reflections of the early childhood care and education landscape in Singapore as it has evolved over the last decade. The discussion will draw on findings of the study Vital Voices for Vital Years 2 (2019) to explicate the issues, debates and challenges facing the early childhood care and education sector. It argues that recent developments in the sector with stepped increases in government funding and strategic policy development, augmented by the establishment of national agencies committed to improving the quality of care and education, have achieved significant milestones in the country. However, a more critical perspective of the role of early childhood in policy and practice to meet the diverse needs of young children and families is necessary for envisioning education as a pathway to inclusion and social equality, and for building a truly inclusive society.